DIVERSITY AND DISTRIBUTION OF MICROFUNGI FROM DIPTEROCARP FORESTS IN SARAWAK, BORNEO ISLAND (MALAYSIA).: Keanekaragaman dan Distribusi mikrofungi dari hutan dipterokarpa di Sarawak, Pulau Borneo (Malaysia). - A. A., Lateef; M., Sepiah; M. H., Bolhassan (Malaysian Journal of Science, 2016)
South-east Asian dipterocarp forests contain plant species that are vulnerable and at risk of extinction. Microfungi, as important decomposers and sources of useful metabolites, have not been well studied in regards to their diversity and distribution in the South-east Asian dipterocarp forests. This study reports the microfungal species associated with dominant and vulnerable plant species in two dipterocarp forests, namely Gunung Gading and Kubah National Parks, in Sarawak on the Borneo Island. Green leaves and litters of five host plants, namely Baccaurea sp., Macaranga triloba (Thunb.) MÃ¼ll.Arg., Macaranga sp., Shorea macrophylla (de Vr.) Ashton and Syzygium sp., were incubated on water agar and malt extract agar. A total of 171 fungal taxa were recorded on the five host plants, during two visits, each to both forests. Syzygium sp. had the highest microfungal diversity of 84 taxa followed by 80 taxa on Macaranga sp., 53 taxa on Baccaurea sp., 43 taxa on M. triloba and the lowest, 35 taxa, on Shorea macrophylla. Pestalotiopsis spp., Oidiodendron spp., Graphium spp., and Mycelia sterilia were the most frequently isolated microfungal species from all the five host plants. There was a high microfungal similarity between Syzygium sp. and Macaranga sp. with 34 taxa common to both plants. The lowest similarity was recorded between S. macrophylla, M. triloba and Baccaurea sp. with only 13 taxa common between them. This is the first report on microfungi associated with dominant and vulnerable plant species in South-east Asian dipterocarp forests; an important record of the fungal diversity on these plants and an exposition on microfungi in Sarawak, Borneo Island, Malaysia. Keywords: Microfungi, Macaranga, Shorea, Baccaurea, Syzygium